Ultra‐High Electrical Conductivity in Filler‐Free Polymeric Hydrogels Toward Thermoelectrics and Electromagnetic Interference Shielding. Issue 12 (10th February 2022) - Wang, Jing; Li, Qing; Li, Kuncai; Sun, Xu; Wang, Yizhuo; Zhuang, Tiantian; Yan, Junjie; Wang, Hong
Abstract: Conducting hydrogels have attracted much attention for the emerging field of hydrogel bioelectronics, especially poly(3, 4‐ethylenedioxythiophene): poly(styrene sulfonate) (PEDOT:PSS) based hydrogels, because of their great biocompatibility and stability. However, the electrical conductivities of hydrogels are often lower than 1 S cm −1 which are not suitable for digital circuits or applications in bioelectronics. Introducing conductive inorganic fillers into the hydrogels can improve their electrical conductivities. However, it may lead to compromises in compliance, biocompatibility, deformability, biodegradability, etc. Herein, a series of highly conductive ionic liquid (IL) doped PEDOT:PSS hydrogels without any conductive fillers is reported. These hydrogels exhibit high conductivities up to ≈305 S cm −1, which is ≈8 times higher than the record of polymeric hydrogels without conductive fillers in literature. The high electrical conductivity results in enhanced areal thermoelectric output power for hydrogel‐based thermoelectric devices, and high specific electromagnetic interference (EMI) shielding efficiency which is about an order in magnitude higher than that of state‐of‐the‐art conductive hydrogels in literature. Furthermore, these stretchable (strain >30%) hydrogels exhibit fast self‐healing, and shape/size‐tunable properties, which are desirable for hydrogel bioelectronics and wearable organic devices. The results indicate that these highly conductive hydrogels are promising in applications such as sensing, thermoelectrics, EMI shielding, etc. Abstract : PEDOT:PSS hydrogels exhibit high conductivities up to ≈305 S cm −1, which is ≈8 times higher than the record of polymeric hydrogels without conductive fillers. The high electrical conductivity results in enhanced areal thermoelectric output power for hydrogel‐based thermoelectric devices, and high specific electromagnetic interference shielding efficiency (an order in magnitude higher than that of reported of state‐of‐the art conductive hydrogels).